Product Market Competition and Employer Provided Training in Germany - John S. Heywood; Uwe Jirjahn; Annika Pfister (Global Labor Organization (GLO), 2017)
Using German establishment data, this paper examines the relationship between product market competition and the extent of employer provided training. We demonstrate that high product market competition is associated with increased training except when the competition is so severe as to threaten liquidation to a firm. We take this as evidence of an inverted U-shaped relationship. We also make clear that while this relationship is very evident for the service sector it is largely missing for manufacturing where we confirm earlier results of no relationship.
Keywords: J24; L00; M53; 330; Competition; Employer Provided Training; Manufacturing; Services